KINSHIP TERMS IN JAPANESE AND KAZAKH PAREMIAES - Amantay, Zh (Journal of Oriental Studies, 2016)
This article discusses the kinship terms, which constitute a part of the Japanese and Kazakh proverbs. The purpose of research is to determine the frequency of use of kinship terms in Japanese and Kazakh paremiaes. As a result of the study of paremiaes with terms of kinship in two languages, the following two group have been identified: 1) paremias with terms of consanguinity; 2) paremiaes with terms of marital relationship. The article also contains a table showing the quantitative analysis of paremiaes.